A novel and efficient approach for the synthesis of new halo substituted 2-arylpyrazolo[4,3-c] coumarin derivatives - Lokhande, Pradeep; Hasanzadeh, Kamal; Konda, Shankaraiah Guruvaiah (European Journal of Chemistry, 2011)
A convenient protocol for the efficient synthesis of 2-arylpyrazolo[4,3-c]coumarins is described. The synthesis route involves molecular iodine catalyzed oxidative cyclization of 1-phenyl-3-(2’-hydroxyaryl)-4-formyl pyrazoles in dimethylsulfoxide. During the lactonisation of 4-formylpyrazoles, we found that iodine was incorporated into the unsubstituted O/P position of the 3-(2’-hydroxyaryl) group. Under similar conditions o-allyloxy derivative of pyrazoles gave same corresponding lactone derivatives by deallylation, lactonisation, and iodination in one step.